Incidence of adrenal gland tumor as a second primary malignancy: SEER-based study. Issue 10 (October 2018) - Rashed, Wafaa M; Saad, Anas; Al-Husseini, Muneer; Galal, Ahmed Mahmoud; Ismael, Assem Mohamed; Al-Tayep, Ahmed M; El Shafie, Ayman; Ali, Mahmoud Ahmed; Alfaar, Ahmad Samir
Abstract : Purpose: Advances in cancer treatment achieved during the past decades have resulted in increased survival of most pediatric and adult patients that suffered from different adrenal tumor types. This article reviews the incidence and survival of adrenal gland tumors as second primary tumors, according to data from the Surveillance, Epidemiology, and End Results (SEER) database. Methods: The SEER 13 Registries Database from 1992 to 2013 was used. All primary cancer sites were selected using the multiple primary standardized incidence ratios (MP-SIR) session. Results: Data for a total of 2, 887, 468 persons with cancer were reviewed; 117 of whom had suffered second primary adrenal tumors. The overall SIR of adrenal gland tumor as a second primary was 1.5. A high incidence ratio of the event was detected in specific primary tumor sites: hypopharynx (observed/expected (O/E) = 44.6); other endocrine tissue (including the thymus) (O/E = 38.3); small intestine (O/E = 8.9); liver (O/E = 8.7); stomach (O/E = 5); nodal NHL (O/E = 3.8); kidney and renal pelvis (O/E = 3.2) and breast (O/E = 1.8). Conclusion: The underlying shared mechanisms should be investigated between adrenal tumors and hypopharyngeal, endocrine and other tumors. Racial disparity is an important challenge in cancer treatment at the United States and should be taken into consideration in the design of cancer prevention programs. This could be achieved through follow-up programs at specialized national cancer networks, especially for rare tumors like adrenal gland.